Description of oral cavity morphology, development and redescription of the tadpole of Bokermannohyla circumdata (Cope, 1870) (Amphibia: Anura: Hylidae) - Mongin, Marcelle Mantoanelli; Carvalho-e-Silva, Ana Maria Paulino Telles de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
Following is a redescription of the tadpole of Bokermannohyla circumdata from Serra dos Órgãos National Park, Teresópolis, Rio de Janeiro, Brazil, with data on spawning, development, variation in labial teeth formula and oral cavity morphology.
Keywords: Atlantic Forest; Spawning; Metamorphosed froglet; Brazil; Serra dos Órgãos National Park